2022
DOI: 10.14429/djlit.42.2.17558
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Support Through Technologies for Persons with Disabilities in Libraries

Abstract: This paper aims to give a brief about the services provided by libraries to disable library users using software and hardware technologies. In this era, the development of technologies, information and communication technologies, etc., is widespread and being disseminated and published globally. Usually, it is convenient for a library professional to differentiate between individuals in need of assistance. This paper emphasises specialised equipment, technologies, and services that provide a barrier-free envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Technology also could help create an equal opportunity and access for learning and access to the curriculum for all (Collinger et al, 2013). Chaurasia & Singh (2022) stated that assistive technology could help people with disabilities meet their needs quickly and effectively. Many organizations have defined assistive technology such as (1) The American Library Association (ALA) defines assistive technology as computer-based technology used to make it compatible with certain types of people, such as the disabled and enhance their potential.…”
Section: Background Study Assistive Technology In Special Educationmentioning
confidence: 99%
“…Technology also could help create an equal opportunity and access for learning and access to the curriculum for all (Collinger et al, 2013). Chaurasia & Singh (2022) stated that assistive technology could help people with disabilities meet their needs quickly and effectively. Many organizations have defined assistive technology such as (1) The American Library Association (ALA) defines assistive technology as computer-based technology used to make it compatible with certain types of people, such as the disabled and enhance their potential.…”
Section: Background Study Assistive Technology In Special Educationmentioning
confidence: 99%
“…AT has become increasingly important for VIUs to access library resources and participate in various activities. It was found that AT could provide a barrier-free environment to the VIUs in libraries, and using appropriate AT in libraries could enhance the learning abilities of VIUs (Chaurasia and Singh, 2022; Bhardwaj, 2021). It is observed that most VIUs depend on their respective libraries to fulfil their information needs (Khowaja and Fatima, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%